THERMOSENSITIVE HYDROGELS–A POTENTIAL CARRIER FOR THE DELIVERY OF DRUGS AND MACROMOLECULES - SAHOO, SOUMYA RANJANA; M., MOTHILAL; B., PRIYADHARSHINI; N., DAMODHARAN (International Journal of Applied Pharmaceutics, 2021)
In this review, the authors have discussed scientific advances in thermosensitive hydrogels over the past two decades. The ability of the thermo-sensitive hydrogel to undergo rapid changes with response to temperature makes it an attractive candidate for many biomedical applications such as targeted drug delivery, wound healing, soft contact lenses, sensors, tissue regeneration, gene, and protein delivery. This review aims to deliver a brief overview of gelation properties, merits, and demerits of various natural and synthetic thermo-sensitive polymers that have significant clinical relevance. The report emphasizes the importance of injectable thermosensitive hydrogels, as it can offer improved solubility of hydrophobic drugs and site-specificity, extended-release of drugs and macromolecules, improved safety, and local administration of drugs. The authors has also provided a commentary on the delivery of drugs or macromolecules from thermo-sensitive hydrogels through various approaches. This review highlights the current status of research in thermo-sensitive hydrogels and emphasizes the importance of developing nontoxic thermo-sensitive hydrogels, dual responsive, and multi-responsive hydrogel systems.